Pengaruh Citra Merek, Kualitas Produk dan Persepsi Harga Terhadap Keputusan Menggunakan Jasa Kurir Jne, Agen Jasafa Jatiasih, Bekasi, Jawa Barat - Elfa Setiawan (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2018)
This study aimed to determine the effect of brand image, product quality, and price perception on the decision to use JNE courier services of Jasafa Agent Jatiasih, Bekasi, West Java area and to analyze the most dominant factor in purchasing decision to use JNE’s services. Samples of this study were  200 consumers who came to send their goods or documents to JNE Jatiasih, Bekasi region for the period of November to December 2016. Incidental sampling technique applied to collect questionnaires from the consumers and the method of data analysis used in this study was descriptive statistical analysis that was Structural Equation Modeling (SEM) using Lisrel software version 8.80.             The result of the research showed that brand image and price perception have significant influence on purchasing decision. Meanwhile the quality product did not have significant influence on  purchasing decision.